Lactacidemic variation and movement patterns during anaerobic power test - Andrade, Vitor L. de [UNESP]; Papoti, Marcelo; Zapaterra Campos, Eduardo [UNESP]; Kalva-Filho, Carlos A.; Bucken Gobbi, Ronaldo [UNESP]; Palucci Vieira, Luiz H.; Souza Bedo, Bruno; Pereira Santiago, Paulo R. (Edizioni Minerva Medica, 2018)
BACKGROUND : After the Running Anaerobic Sprint Test (RAST) high blood lactate concentrations ([La-]) are found. However, no study verified the behavior of this metabolite during RAST. For this, the aim of the present study was to verify the implications of increase [La-] on movement patterns' in RAST performance. METHODS: Six healthy and active individuals (21.8 +/- 3.1 years, 70.9 +/- 10.8 kg and 179.7 +/- 3.3 cm) executed a standardized warm-up. Two minutes later, subjects performed RAST composed of six maximal 35-m bouts separated by 10 s of passive recovery. During RAST, 14 cameras monitored the subjects to determine tridimensional and bi-dimensional mechanics. [La-] were determined before warm-up, between each bout and after RAST. RESULTS: Significant difference in performance were found after the fifth (5.1 +/- 0.1 s) and sixth (5.4 +/- 0.3 s; P<0.04) bout in relation to the first up to fourth effort. Fatigue indexes (FI % and FIREAL) were higher from fifth bout (19.2 +/- 9.4%; 19.3 +/- 10.9%; P<0.05). No significant difference was observed in [La-] on fifth and sixth bout (8.2 +/- 2.4 mM and 9.2 +/- 2.1 mM) however, both were different from all other bouts. Flight time was different between the fifth bout (0.16 +/- 0.03 s) when compared with the first (0.12 +/- 0.01 s; P=0.01) and second (0.13 +/- 0.02s; P=0.03) bouts. CONCLUSIONS: RAST performance can be influenced by physiological changes. Biomechanical behavior does not alter performance without a sum of physiological events.
Keywords: Soccer; Basketball; Football; Running; Lactates